Prehospital management of exertional heat stroke at sports competitions for Paralympic athletes. Issue 11 (7th October 2021) - Hosokawa, Yuri; Adami, Paolo Emilio; Stephenson, Ben Thomas; Blauwet, Cheri; Bermon, Stephane; Webborn, Nick; Racinais, Sebastien; Derman, Wayne; Goosey-Tolfrey, Victoria L
Abstract : Objectives: To adapt key components of exertional heat stroke (EHS) prehospital management proposed by the Intenational Olympic Committee Adverse Weather Impact Expert Working Group for the Olympic Games Tokyo 2020 so that it is applicable for the Paralympic athletes. Methods: An expert working group representing members with research, clinical and lived sports experience from a Para sports perspective reviewed and revised the IOC consensus document of current best practice regarding the prehospital management of EHS. Results: Similar to Olympic competitions, Paralympic competitions are also scheduled under high environmental heat stress; thus, policies and procedures for EHS prehospital management should also be established and followed. For Olympic athletes, the basic principles of EHS prehospital care are: early recognition, early diagnosis, rapid, on-site cooling and advanced clinical care. Although these principles also apply for Paralympic athletes, slight differences related to athlete physiology (eg, autonomic dysfunction) and mechanisms for hands-on management (eg, transferring the collapsed athlete or techniques for whole-body cooling) may require adaptation for care of the Paralympic athlete. Conclusions: Prehospital management of EHS in the Paralympic setting employs the same procedures as for Olympic athletes with some important alterations.